Depcition of Chamunda with multiple arms - Temples of India Project Team (Jio Institute, 2024)
On the north wall of the garbhagriha (sanctum sanctorum), Chamunda is depicted with multiple arms, standing on a human body. All her arms are broken except her upper three arms, one of which is carrying a shield. She has a halo around her head with flying celestial shown on both sides of her halo. She has a jatamukuta (crown of matted hair) decorated with a human skull. Her face is damaged, but one can see bulging eyes. She has a thin body with shrivelled breasts and a sunken belly.